Host-guest complexation of a nitroheterocyclic compound with cyclodextrins: a spectrofluorimetric and molecular modeling study - Grillo, Renato [UNESP]; de Melo, Nathalie F. S.; de Araujo, Daniele R.; Trossini, Gustavo H. G.; da Cunha, Elaine F. F.; Ramalho, Teodorico de Castro; Fraceto, Leonardo Fernandes [UNESP] (Springer, 2010)
Nitroheterocyclic compounds (NC) were candidate drugs proposed for Chagas disease chemotherapy. In this study, we investigated the complexation of hydroxymethylnitrofurazone (NFOH), a potential antichagasic compound, with alpha-cyclodextrin (alpha-CD), beta-cyclodextrin (beta-CD), Hydroxypropyl-beta-cyclodextrin (HP-beta-CD), Dimethyl-beta-cyclodextrin (DM-beta-CD) and gamma-cyclodextrin (gamma-CD) by fluorescence spectroscopy and molecular modeling studies. Hildebrand-Benesi equation was used to calculate the formation constants of NFOH with cyclodextrins based on the fluorescence differences in the CDs solution. The complexing capacity of NFOH with different CDs was compared through the results of association constant according to the following order: DM-beta-CD > beta-CD > alpha-CD > HP-beta-CD > gamma-CD. Molecular modeling studies give support for the experimental assignments, in favor of the formation of an inclusion complex between cyclodextrins with NFOH. This is an important study to investigate the effects of different kinds of cyclodextrins on the inclusion complex formation with NFOH and to better characterize a potential formulations to be used as therapeutic options for the oral treatment of Chagas disease.
Keywords: Nitroheterocyclic compound; Cyclodextrins; Fluorescence spectroscopy; Molecular modeling; Inclusion complex